2013
DOI: 10.1080/01431161.2013.787504
|View full text |Cite
|
Sign up to set email alerts
|

Loop Current excursions and ring detachments during 1993–2009

Abstract: Linkages between the variability of Loop Current (LC) surface dynamics, LC ring detachments, and the mean sea height anomaly in the Gulf of Mexico (GOM) are explored using a new methodology that locates the LC fronts and detects the shedding of LC rings. Based on satellite altimetry observations and dynamic height gradient, this methodology allows the determination of the dynamic structure in the region from 1993 to 2009. Northward penetration of the LC was found to be seasonal, with a tendency to increase dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
(29 reference statements)
1
22
1
Order By: Relevance
“…LindoAtichati et al (2012) classified altimeter SSH fields and derived cyclonic and anticyclonic eddies into core and boundary regions, using the standard deviation of SSH and the standard deviation of the absolute value of the gradient of SSH in the Gulf of Mexico. This method was used again by Lindo-Atichati, Bringas, and Goni (2013) for studying the loop current in the Gulf of Mexico. A simplified version of the zoning approach of Lindo-Atichati et al (2012) using the mean value of SLA within the eddy bounding contour, instead of standard deviation and gradient of SSH of entire region, was followed in this study to delineate eddy zones.…”
Section: Identification Of Eddy Zonesmentioning
confidence: 99%
“…LindoAtichati et al (2012) classified altimeter SSH fields and derived cyclonic and anticyclonic eddies into core and boundary regions, using the standard deviation of SSH and the standard deviation of the absolute value of the gradient of SSH in the Gulf of Mexico. This method was used again by Lindo-Atichati, Bringas, and Goni (2013) for studying the loop current in the Gulf of Mexico. A simplified version of the zoning approach of Lindo-Atichati et al (2012) using the mean value of SLA within the eddy bounding contour, instead of standard deviation and gradient of SSH of entire region, was followed in this study to delineate eddy zones.…”
Section: Identification Of Eddy Zonesmentioning
confidence: 99%
“…The complex LC pattern variations were a subject of many previous studies [e.g., Sturges and Leben , ; Leben , ; Lugo‐Fernández , ]. Particularly, the intrusion, eddy shedding, and retraction processes of the LC are of interest [e.g., Chang and Oey , ; Xu et al ., ; Lindo‐Atichati et al ., ; Dukhovskoy et al ., ]. Lugo‐Fernández and Leben [] found a linear correlation between LC retreat latitude following eddy separation and the subsequent eddy separation period.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, changes in the mean eddy separation period and eddy separation frequency were discussed in Vukovich (2012) and Lindo-Atichati et al (2013). Both studies reported an increase of eddy separation frequency and decrease in the LC's average separation period during the 2000s compared to estimates from an earlier time period of observations.…”
Section: Analysis Of the Lc Stationaritymentioning
confidence: 95%
“…Past studies have used SSH contours for tracking of the LC front in SSH fields assuming that the LC front coincides with a single streamline. Other LC tracking methods have also been proposed (e.g., Andrade-Canto et al, 2013;Lindo-Atichati et al, 2013), and each yields somewhat different results. Thus, metrics for describing LC front positions vary depending on the method used to identify the front.…”
Section: Automated Tracking Of the Loop Current Frontmentioning
confidence: 98%